2007
DOI: 10.1088/0029-5515/47/11/l01
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the magnetic reconnection zone during sawtooth crashes in tokamak plasmas

Abstract: Recent 2D spatially and temporally resolved measurements of electron temperature fluctuations in the tokamak core have revealed new information on the dynamics of the sawtooth crash. Measures of poloidal localization of the reconnection zone are achieved through direct analysis of the 2D data and through an interpolated projection of the q = 1 region. An estimate of the toroidal coverage of the reconnection zone is achieved through analysis of shots exhibiting toroidal rotation in which the helically localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 14 publications
(17 reference statements)
1
40
1
Order By: Relevance
“…This makes our observations relevant to the results of MST [19], where large spontaneous events include mode locking between modes with a range of different m and n numbers. Similar dynamics also appear to be important in recent observations of sawtooth reconnection [22] where higher order modes are observed before and after the reconnection events. In the closed cusp configuration, where the field lines are confined inside the experiment, the coupling between global modes and a current sheet leads to powerful bursts of 3D spontaneous reconnection [1].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This makes our observations relevant to the results of MST [19], where large spontaneous events include mode locking between modes with a range of different m and n numbers. Similar dynamics also appear to be important in recent observations of sawtooth reconnection [22] where higher order modes are observed before and after the reconnection events. In the closed cusp configuration, where the field lines are confined inside the experiment, the coupling between global modes and a current sheet leads to powerful bursts of 3D spontaneous reconnection [1].…”
Section: Discussionsupporting
confidence: 72%
“…On MST, Choi et al [19] found that small sawtooth events are linearly unstable and hence spontaneous, while larger events require a nonlinear mode coupling for the instability to grow. In sawtooth reconnection, detailed measurements by Park et al [9,20,21] and Munsat et al [22] from the TEXTOR tokamak found toroidally localization of the reconnection events, with reconnection starting at specific toroidal locations with both "good" and "bad" curvature. These observations show that the 2D theories may not capture the essential physics to describe the onset of spontaneous reconnection.…”
Section: Introductionmentioning
confidence: 98%
“…Given the results presented regarding 3D effects in magnetic reconnection, as well as the experiments by Park et al [64,65,66], which show that the sawtooth onset is toroidally and poloidally localized, it is clear that 2D theories of the sawtooth are insufficient. Specifically, the theories by Kadomtsev [17] and Wesson [117], which are often used to frame the sawtooth problem, require modification to reflect the new observations of toroidal localization.…”
Section: Applications To Tokamak Plasmasmentioning
confidence: 92%
“…These measurements, which take advantage of advances in electron cyclotron emission imaging [64,65,66], have shown that sawtooth onset is localized both toroidally and poloidally and that the temperature profile flattening is well-organized as opposed to stochastic [67]. The localization is observed even though the magnetic field geometry is mainly 2D.…”
Section: Reconnection In 3dmentioning
confidence: 99%
“…in the direction co-or counter-aligned with the reconnection electric field. Observational signatures of the RR localization (Munsat et al, 2007) and motion in solar flares (Qiu, 2009) and laboratory experiments (Katz et al, 2011) indicate that the reconnection magnetic structure can propagate at a substantial fraction of the local Alvén speed with respect to surrounding plasma, but there have been few numerical studies that have focused on the propagating RR phenomenon (e.g. Lapenta et al, 2006 and references therein).…”
Section: Introductionmentioning
confidence: 99%